2018
DOI: 10.1007/s00018-018-2769-0
|View full text |Cite
|
Sign up to set email alerts
|

The DNA double-strand “breakome” of mouse spermatids

Abstract: De novo germline mutations arise preferentially in male owing to fundamental differences between spermatogenesis and oogenesis. Post-meiotic chromatin remodeling in spermatids results in the elimination of most of the nucleosomal supercoiling and is characterized by transient DNA fragmentation. Using three alternative methods, DNA from sorted populations of mouse spermatids was used to confirm that double-strand breaks (DSB) are created in elongating spermatids and repaired at later steps. Specific capture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Initially, DBrIC was used to demonstrate locus-specific and genome-wide DSBs in human cancer cells. More recently, the approach was harnessed to profile DSB hotspots during the transient genome fragmentation that accompanies post-mitotic chromatin remodeling in mouse spermatids [215,216].…”
Section: Methods For Genome-wide Dsb Profilingmentioning
confidence: 99%
“…Initially, DBrIC was used to demonstrate locus-specific and genome-wide DSBs in human cancer cells. More recently, the approach was harnessed to profile DSB hotspots during the transient genome fragmentation that accompanies post-mitotic chromatin remodeling in mouse spermatids [215,216].…”
Section: Methods For Genome-wide Dsb Profilingmentioning
confidence: 99%
“…Several methods were used to confirm that the transient DNA strand breakage in spermatids also included a significant proportion of DNA double-strand breaks (DSBs). These included neutral comet assay, pulse-field gel electrophoresis [12], γH2AX labelling [13] and qTUNEL assay, whereby double-strand breaks were specifically labelled in solution following a prior step involving DNA nicks and gap filling [14]. Indirect evidence of a DSB repair response based on γH2AX expression must however be taken with caution, as the latter has also been associated with chromatin alteration [15].…”
Section: Dna Double-strand Breaks (Dsbs) Are Intrinsic To the Diffmentioning
confidence: 99%
“…Whereas meiosis may have evolved mechanisms to prevent these error-prone end-joining processes [18,46], haploid spermatids likely cannot avoid such mutagenic repair mechanisms. However, our initial mapping data indicated that the transient post-meiotic DSBs arise preferentially within repeated elements of the genome, which should minimize the genetic threat associated with the DSB formation [12]. It is important that coding sequences be protected from the global DNA fragmentation process, especially because of the general loss in DNA repair capacity that has been observed as the chromatin remodeling in spermatids proceeds to the final steps [47,48,49].…”
Section: Potential Mechanism For Dsbs Formation and Repairmentioning
confidence: 99%
See 2 more Smart Citations